Does body mass index impact assisted reproductive technology treatment outcomes in gestational carriers - Noga Fuchs Weizman; Miranda K. Defer; Janice Montbriand; Julia M. Pasquale; Adina Silver; Clifford L. Librach (BMC, 2020)
Abstract Background The purpose of this study was to assess whether increased body mass index (BMI) negatively affects assisted reproductive technology (ART) outcomes among gestational carriers. Methods A retrospective matched case-control cohort, including all gestational carrier (GC) cycles performed at CReATe Fertility Centre (Toronto, ON, Canada) between 2003 and 2016. Setting A Canadian fertility clinic, with a large surrogacy program. Patients All gestational carriers that had undergone a cycle completed to a transfer at our clinic, and had BMI and outcome data available, were matched by BMI to infertile patients treated at our clinic during the same years provided they had undergone a cycle completed to a transfer, and had outcomes data available. Interventions None. Main outcome measures Clinical pregnancies rates, miscarriage rates and live birth rates. Results BMI was not a reliable prediction factor of any of the measured outcomes. Importantly, the gestational carrier population had better outcomes and a significantly lower overall incidence of maternal, fetal and neonatal complications when compared with infertile patients, treated at our clinic during the same years. Conclusion BMI is not a reliable predictor of outcomes among gestational carriers.